A systematic integrated analysis of brain expression profiles reveals YAP1 and other prioritized hub genes as important upstream regulators in Alzheimer's disease. Issue 2 (16th September 2017) - Xu, Min; Zhang, Deng‐Feng; Luo, Rongcan; Wu, Yong; Zhou, Hejiang; Kong, Li‐Li; Bi, Rui; Yao, Yong‐Gang
Abstract: Introduction: Profiling the spatial‐temporal expression pattern and characterizing the regulatory networks of brain tissues are vital for understanding the pathophysiology of Alzheimer's disease (AD). Methods: We performed a systematic integrated analysis of expression profiles of AD‐affected brain tissues (684 AD and 562 controls). A network‐based convergent functional genomic approach was used to prioritize possible regulator genes during AD development, followed by functional characterization. Results: We generated a complete list of differentially expressed genes and hub genes of the transcriptomic network in AD brain and constructed a Web server (www.alzdata.org ) for public access. Seventeen hub genes active at the early stages, especially YAP1, were recognized as upstream regulators of the AD network. Cellular assays proved that early alteration of YAP1 could promote AD by influencing the whole transcriptional network. Discussion: Early expression disturbance of hub genes is an important feature of AD development, and interfering with this process may reverse the disease progression.